Synthesis, Characterization and Biological Activities of Mixed Ligand Complexes of Mannich Base Derived from 2-Mercaptobenzothiazole - Al-Hasani, Rehab A M; Shaheen, Eiman S A (Al-Nahrain Journal of Science, 2018)
The compound (2-mercaptobenzothiazole) (2-MBT) react with formaline and dicyclohexyl amine to form new mannich base [3-dicyclohexyl amino methyl -2- mercaptobenzothiazole] [E]. The product was characterized by (FT-IR ,1H.N.M.R and C.H.N.S). (E) was used as a ligand for preparation mono ligand complexes of metal ions [Mn(II), Co(II), Ni(II), Cu(II) and Zn(II)] on the one hand and mixed ligand complexes of the same metal ions using the preparation mannich base (E) as a primary ligand and the amino acid tryptophan (Trp.) as a scondary ligand on the other hand. The prepared mono and mixed ligand complexes were isolated in the solid state and characterized by (FT-IR and Uv-Vis) Spectroscopy, (elemental analysis and flame atomic absorption) techniques as well as (magnetic susceptibility and conductivity) measurements. Based on the results of these diagnoses which showed that the metal ions was coordinated with (E) by nitrogen atom of amino methyl group and sulfer atom of thiocarbonyl group on the mono and mixed ligand complexes, in addition of coordination of (Trp.) on the mixed ligand complexes by oxygen atom of carboxyl group and nitrogen atom of the free amine group. The antibacterial activity for ligands (E and Trp.) and their mono and mixed ligand complexes were studied against two selected micro-organisms (Escherichia coil ) and (staphylococcus aureus), the minimal inhibitory concentration (MIC ) have been also studied to determined the low concentration for inhibition , two antibiotics (Ampicillin and Amoxicillin) have been chosen to compare their activity with those of the new compounds. The results showed higher activity of the new compounds relative to the chosen antibiotics .Furthermore the antifungl activity against two micro-organism (penicillum Spp and Aspergillus flavus) were studied for ligands (E and Trp.) and their mono and mixed ligand complexes. The results showed great enhancement of activity of the all complexes relative to that of their respective ligands. This was attributed to the synergetic effect between the metel ion and the ligand, in addition to the differences in the structural varities.